Natural occurrence of Ochratoxin A in musts, wines and grape vine fruits from grapes harvested in Argentina - Ponsone, María Lorena; Chiotta, María Laura; Combina, Mariana; Torres, Adriana; Knass, Patricia; Dalcero, Ana María; Chulze, Sofia Noemí (2017)
In this study, ochratoxin A (OTA) occurrence in Argentinean musts, wines and dried vine fruits was evaluated, alongside with the performance of OchraStarTM columns for OTA extraction. In all the three matrices analyzed, the OchraStarTM columns showed good performance. The analysis of natural occurrence of OTA in the red must and the red wine samples showed low incidence with low levels of mean OTA contamination (0.12 ng/mL and 0.37 ng/mL, respectively), while 60% of the dried vine fruit samples were contaminated with OTA, in levels ranging from 0.26 to 20.28 ng/g